2021
DOI: 10.1002/alz.12339
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and missing cognitive test scores in a population‐based study of older adults: The Atherosclerosis Risk in Communities neurocognitive study

Abstract: Introduction:Hearing impairment is associated with poor cognitive test performance in older adults. However, hearing's impact on cognitive test completion is poorly described, and missing cognitive data due to hearing impairment could misestimate the association. Methods:We investigated if hearing impairment is associated with missing neurocognitive scores in 3678 adults (72-94 years). Hearing impairment was defined by the better-ear pure tone average of speech-frequency thresholds (0.5-4 kHz) >25 decibels.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…For example, in a study of cognitive performance in patients with chronic kidney disease, nearly half of the original sample was excluded by investigators due to “visual, motivational, or motor difficulties.” 7 Alternatively, if there is a causal relationship between sensory impairment and ADRD, exclusion of participants with sensory impairment could have the opposite effect, resulting in an underestimation of the prevalence of ADRD and cognitive impairment. In support of this possibility, we recently found that older adults with hearing loss in the Atherosclerosis Risk in Communities study were less likely to complete cognitive testing than older adults without hearing loss, and that this missing data resulted in an underestimation of the hearing loss–cognitive performance relationship by ≈30% 8 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in a study of cognitive performance in patients with chronic kidney disease, nearly half of the original sample was excluded by investigators due to “visual, motivational, or motor difficulties.” 7 Alternatively, if there is a causal relationship between sensory impairment and ADRD, exclusion of participants with sensory impairment could have the opposite effect, resulting in an underestimation of the prevalence of ADRD and cognitive impairment. In support of this possibility, we recently found that older adults with hearing loss in the Atherosclerosis Risk in Communities study were less likely to complete cognitive testing than older adults without hearing loss, and that this missing data resulted in an underestimation of the hearing loss–cognitive performance relationship by ≈30% 8 …”
Section: Introductionmentioning
confidence: 94%
“…In support of this possibility, we recently found that older adults with hearing loss in the Atherosclerosis Risk in Communities study were less likely to complete cognitive testing than older adults without hearing loss, and that this missing data resulted in an underestimation of the hearing loss-cognitive performance relationship by ≈30%. 8 Discriminating between the contributions of sensory impairment to testing bias and the contributions of true cognitive impairment will allow us to better target and remediate modifiable pathways. Despite the importance of this distinction, few studies have carefully considered the potential impact of sensory impairment on cognitive testing.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence shows that noise may cause an increase in stress hormone release and in circulating angiotensin II (Ang II) levels with significant stress-induced increase in blood pressure (36). The effects of noise exposure on cognitive function (18), mental health (40) and spiritual wellbeing (41) may also play an important role in the process of occupational noise exposure affecting cardiovascular health. Surprisingly, we found that protective measures such as wearing ear muffs and earplugs could not reduce the risk of hypertension in workers.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern industrialization, occupational noise exposure related to occupational injury has gradually attracted public attention. It has long been established that occupational noise exposure may induce adverse auditory health effects (14)(15)(16)) and non-auditory health effects (17)(18)(19)(20), while the effect of occupational noise exposure on hypertension has been controversial. Existing studies report conflicting results on it (21-23).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ARHL increased with age, particularly after the mid-50s. Approximately 40% of individuals aged 65 or older have impaired hearing ( Patel and McKinnon, 2018 ), which can substantially contribute to depression, social isolation, and a high risk of dementia ( Loughrey et al, 2018 ; Deal et al, 2021 ). The pathophysiological mechanisms involved in ARHL include oxidative stress, excitotoxicity, inflammation, and ischemia, resulting in age-related changes in specific locations within the cochlea (auditory hair cells, stria vascularis, spiral ganglion neurons, and supporting cells) ( Pool and Meagher, 1990 ; Mazelova et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%